PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN MINAT BELAJAR DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 1 KOTA TANGERANG SELATAN - Januri; Arief, Armai; Saleh, Marhamah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low interest in learning of students due to the dominance of conventional teacher-centered approaches is a serious challenge in learning Aqidah Akhlak in madrasas, which ultimately hinders the achievement of optimal learning achievements. This study aims to analyze the influence of the Project Based Learning (PjBL) learning model on student learning achievement, the influence of PjBL on students' learning interests, and the relationship between learning interest and learning achievement in the subject of Aqidah Akhlak in MAN 1 South Tangerang City. The study used a correlational quantitative approach with a population of 589 students and a sample of 59 students selected through a combination of area sampling, proportional sampling, and random sampling techniques. Data collection was carried out using a questionnaire based on the Likert Scale, and the data analysis included product moment correlation tests, linear regression analysis, and determination coefficients. The results showed that: (1) PjBL had a positive and significant effect on student learning achievement with a correlation coefficient of r = 0.454 and a determination coefficient of 20.6%; (2) PjBL has a positive and significant effect on students' learning interest with r = 0.514 and determination of 26.4%; and (3) interest in learning has a positive and significant effect on learning achievement with r = 0.627 and determination of 39.3%. This research contributes to filling the research gap related to the simultaneous study between PjBL, learning interest, and learning achievement in the context of Aqidah Akhlak at the Madrasah Aliyah level, as well as providing empirical recommendations for teachers to optimize project-based learning strategies to improve the quality of education in madrasas.